Medical And Economic Management Aspects of Activities in Selected Countries in Face of First Wave of COVID-19 Pandemic. Comparison Of Activities Undertaken in Poland, Germany and The United States - Marcin BOBRUK; Zbigniew WISNIEWSKI (Communications of International Proceedings, 2021)
The growing number of people infected with SARS-CoV-2 resulted in the introduction of more and more restrictions by policy makers around the world, which had its medical justification. The article first discusses the possibility of effective treatment of SARS-CoV-2 infection. Then it reviews the available information in the field of medicine and indicates methods of dealing with specific cases. Next, the article presents economic and management activities related to COVID-19 in selected countries, i.e. Poland, Germany and the United States. It was analyzed how these countries reacted to negative information related to the pandemic (initially) and the epidemic itself (later). Poland, Germany and the USA first had to make a decision about imposing lockdown, and then – after a few months – opening again their economies. Due to the large amount of information related to both medical, economic and managerial aspects related to COVID-19, it was necessary to limit the exploratory study. In the case of medical issues, reference was made primarily to the effectiveness of the treatment of SARS-CoV-2 infection.
Keywords: covid; management; pandemic; treatment; SARS-CoV-2; economic; restrictions; health systems